PERSUASIVE STRATEGIES IN WOMAN COSMETICS ADVERTISEMENT OF SKIN WHITENING PRODUCT ON TELEVISION COMMERCIAL - Dewi Anjani Purba and Sumarsih (LINGUISTICA, 2017)
This research is aimed at describing persuasive strategies in woman cosmetics advertisement, elaborating the ways of the strategies are used and investigating the reason for the use of strategies. The study is based on a descriptive qualitative method, The researcher analyzed through describing and explaining data based on persuasive strategies by Aristotle (1854).There are about 50 samples of woman cosmetics in skin whitening product from different brand. Those advertisements are in the form of video taken from the official website of the product, youtube, and watching the advertisement in television. The result of this study found that there were 32 utterances that categorized as Ethos, 12 as Pathos, and 6 as Logos. There are two process happen in this persuasive strategies,The Elaboration Likelihood Model (Central & Peripheral Route) and Heuristic Systematic Model (Heuristically Processing & Systematically Processing). Central Route 31, Peripheral Route 19. HeuristicallyProcessing 12 and Systematically Processing 38. Reasons for the use of Central Route in the advertisement should be relevant, any facts. Peripheral Route, irrelevant, and no fact. Heuristically Processing, message by expert or endorse by artist, not always giving facts. Systematically Processing, relevant, motivate the costumers, any facts.